2021
DOI: 10.1073/pnas.2022216118
|View full text |Cite
|
Sign up to set email alerts
|

Human impacts and Anthropocene environmental change at Lake Kutubu, a Ramsar wetland in Papua New Guinea

Abstract: The impacts of human-induced environmental change that characterize the Anthropocene are not felt equally across the globe. In the tropics, the potential for the sudden collapse of ecosystems in response to multiple interacting pressures has been of increasing concern in ecological and conservation research. The tropical ecosystems of Papua New Guinea are areas of diverse rainforest flora and fauna, inhabited by human populations that are equally diverse, both culturally and linguistically. These people and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Interdisciplinary research between social scientists, geographers, archaeologists, and earth scientists is required to better constrain the relationships between humans and karst landscapes. Human activity through the Anthropocene is negatively impacting the karst landscape (Beach et al., 2015; Long et al., 2021). This delicate environment is susceptible to soil degradation, sinkhole development, groundwater contamination, and depletion in groundwater levels.…”
Section: Exploring the Carbonate Endmembermentioning
confidence: 99%
“…Interdisciplinary research between social scientists, geographers, archaeologists, and earth scientists is required to better constrain the relationships between humans and karst landscapes. Human activity through the Anthropocene is negatively impacting the karst landscape (Beach et al., 2015; Long et al., 2021). This delicate environment is susceptible to soil degradation, sinkhole development, groundwater contamination, and depletion in groundwater levels.…”
Section: Exploring the Carbonate Endmembermentioning
confidence: 99%
“…Schiefer et al (2013) reported a steadily increasing lake sedimentation rate in the late 20th century in western Canada linked to the oil, gas, and timber extraction industries. Deforestation in much of the rest of the world increased rapidly during the late 20th century, which has frequently been recorded in lacustrine records (e.g., Roulet et al, 2000;Dearing and Jones, 2003;Long et al, 2021). Now, the Global South, consisting of many developing nations in the tropics, has overtaken developed nations in population growth and resource consumption (Chant and McIlwaine, 2009;Adams et al, 2019;State of the Tropics, 2020).…”
Section: Recent Sediment Accumulation Rates Increasing In Tropical Lo...mentioning
confidence: 99%
“…Interdisciplinary research between social scientists, geographers, archaeologists, and earth scientists is required to better constrain the relationships between humans and karst landscapes. Human activity through the Anthropocene is negatively impacting the karst landscape (Long et al, 2021;Beach et al, 2015). This delicate environment is susceptible to soil degradation, sinkhole development, groundwater contamination, and depletion in groundwater levels.…”
Section: Humans and The Carbonate Czmentioning
confidence: 99%